Protocolos de roteamento: características e benefícios - Carraro, Kleverton Silva (2014)
This monograph deals with the study of the characteristics of routing protocols and their benefits. Three routing protocols for this study will be discussed, the protocols that will be addressed are: RIP, OSPF and EIGRP. The project starts up bibliographic form elements bringing the concepts of each protocol, followed by practice in packet tracer configuration first and then configure the routers. The end result will show how each protocol behaves within the routers, what the benefits of each and when to use each one of them will show a difference between each of them which will be reported on the best protocol should be used and in which scenario they behave better.